The attitudes of teachers and students towards ‘one-to-five’ students’ network: Implications for students’ learning - Nigusse Weldemariam Reda; Tsegay Girmany Hagos (Bahir Dar Journal of Education)
This study was conducted to explore the attitudes of teachers and students towards the one-to-five students' network. Cognizant of this, survey research design and quantitative research approach were followed to meet the purposes of the study. Accordingly, 471 teachers and 476 students were selected from 17 secondary and 43 upper primary schools in Tigray through a multistagecluster sampling. Data were collected through self-developed questionnaire. Finally, data analyzed through mean and independent samples t-test revealed that teachers and students had positive attitudes towards the one-to-five students' network. Moreover, even if there were no significant attitude differences among participants of similar cycles, a statistically significant attitude differences were found among upper primary and secondary school participants. The differences were found in favor of the upper primary school teachers and students. Finally, the implications of the findings for the improvement of students' learning are highlighted. This study was conducted to explore the attitudes of teachers and students towards the one-to- five students' network. Cognizant of this, survey research design and quantitative research approach were followed to meet the purposes of the study. Accordingly, 471 teachers and 476 students were selected from 17 secondary and 43 upper primary schools in Tigray through a multistage-cluster sampling. Data were collected through self-developed questionnaire. Finally, data analyzed through mean and independent samples t-test revealed that teachers and students had positive attitudes towards the one-to-five students' network. Moreover, even if there were no significant attitude differences among participants of similar cycles, a statistically significant attitude differences were found among upper primary and secondary school participants. The differences were found in favor of the upper primary school teachers and students. Finally, the implications of the findings for the improvement of students' learning are highlighted.